EVALUASI STRATEGI MEDIA SOSIAL PADA PT XL AXIATA - , Mohammad Fardani Dzulhikam ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Social media is not only used by individuals but also organizations have aware it roles to engage their stakeholders: customer, employees and other related party. XL Axiata is a telecommunication company in Indonesia that have utilized social media to engage its costumers. The objective of this research is to evaluate social media strategy that is used by XL Axiata. This research shall describe social media strategy that is used by XL Axiata, what became the basis of the strategy formulation and what are the social media ecosystems that are used by XL. It will then be analyzed to determine whether the strategy has been well formulated, well executed, and gave satisfactory outcome. The results showed that XL formulated its social media strategic based on its four key transformation initiatives in 2011. The initiatives are : Shifting the focus from Voice and Short Message Service to Mobile Data Services, Enhancing service quality, Increasing customer retention and Strengthening brand position. XLâs social media strategy are already on ideal phase, the phase where social media strategy is aligned with business strategy. XL also had adopted four pillar of social media which are: communication, collaboration, education and entertainment. The outcome that has been gain from social media strategy are: mobile data users composition increase, data related revenue composition increase and strengthening XLâs as quality service provider.